The Realization of the Derivational and the Inflectional Processes in the Students’ Writing - Sadam Pamungkas; Dwi Rukmini; Frimadhona Syafri (Universitas Negeri Semarang, 2022)
In learning a language, students are supposed to study linguistics in order to be able to recognize the root of words, how they are formed, and the context of language. This study aimed to explain the realization of the derivational process, the inflectional process, and the causes of the error in the students’ writing. This study used a descriptive qualitative design. The researchers analyzed the students’ writing essays written by the XII-graders of the Vocational High School Al-Musyaffa Kendal in the academic year 2021/2022. The instruments are document analysis theory and interview. It used the theory of Dulay et.al. (1982). The findings demonstrate that the students made errors that belong to both the derivational and the inflectional processes. Most of the students made errors in the omission of derivation, yet they made fewer errors in the addition and malformation of derivation. Besides, there were many problems in dealing with the inflection. Most of the students were confused about how to deal with the omission of noun inflection and the omission of verb inflection. Nevertheless, they made fewer errors in the misordering of verb inflection. In addition, the cause of the error that the students did was mostly carelessness as it occurs due to students’ lack of motivation and less enthusiasm in engaging in the teaching and learning process. Expectantly, this research will provide an essential contribution as a reference in comprehending word formation and contribute to teaching and learning of forming English words.